Analysis of Theme and Rheme in a Selected Social Media Post by Vladimir Putin - Hasibuan, Rafikah; Utari, Putri; Sitorus, Indah Yunita Br.; Rangkuti, Linda Astuti; Zulkarnain, Iskandar (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
This study analyzes the Theme and Rheme of Russian President Vladimir Putin's speech and evaluates its effectiveness. The speech delivered during his annual address to the Federal Assembly in Moscow, the speech often attracted public interest and curiosity about its meaning. It had a significant impact on social media platforms like TikTok and YouTube, becoming viral. This significant attention was why Putin's speech was chosen for this research. The research employed a qualitative approach. The data were viral speech delivered by Putin in Moscow in 2024. Data were collected through observation and analyzed by comparing, describing, classifying, and presenting it using tables and descriptions. The findings showed 1 Unmarked Simple Theme (UST) (11.1%), 3 Unmarked Multiple Themes (UMT) (44.4%), no Marked Simple Theme (MST), and 3 Marked Multiple Themes (MMT) (44.4%) in the speech. The dominance of UMT and MMT was due to the